Impact of nutrition and physical activity on outcomes of hospital-acquired pneumonia - Jin Ho Jang; Taehwa Kim; Hye Ju Yeo; Woo Hyun Cho; Kyung Hoon Min; Jee Youn Oh; Sang-Bum Hong; Ae-Rin Baek; Hyun-Kyung Lee; Changhwan Kim; Youjin Chang; Hye Kyeong Park; et al. (Scientific Reports, 2022)
Abstract Frailty is an important risk factor for adverse health-related outcomes. It is classified into several phenotypes according to nutritional state and physical activity. In this context, we investigated whether frailty phenotypes were related to clinical outcome of hospital-acquired pneumonia (HAP). During the study period, a total of 526 patients were screened for HAP and 480 of whom were analyzed. The patients were divided into four groups according to physical inactivity and malnutrition: nutritional frailty (Geriatric Nutritional Risk Index [GNRI] < 82 and Clinical Frailty Scale [CFS] ≥ 4), malnutrition (GNRI < 82 and CFS < 4), physical frailty (GNRI ≥ 82 and CFS ≥ 4), and normal (GNRI ≥ 82 and CFS < 4). Among the phenotypes, physical frailty without malnutrition was the most common (39.4%), followed by nutritional frailty (30.2%), normal (20.6%), and malnutrition (9.8%). There was a significant difference in hospital survival and home discharge among the four phenotypes (p = 0.009), and the nutritional frailty group had the poorest in-hospital survival and home discharge (64.8% and 34.6%, respectively). In conclusion, there were differences in clinical outcomes according to the four phenotypes of HAP. Assessment of frailty phenotypes during hospitalization may improve outcomes through adequate nutrition and rehabilitation treatment of patients with HAP.